Analysing customer requirements and satisfaction in the furniture industry according to ISO 9000 certification: a case study - Laura Martínez Caro; Enrique Flores López; Jose Antonio Martínez García (Management Letters/Cuadernos de Gestión, 2010)
The need to identify customer requirements and to satisfy them has become the main objective of companies. To manage that activity, that it is commonly associated to the marketing department, is the aim of every quality system, and therefore is a task that comprises the remaining departments of the organization. Through a case study, this paper seeks to identify which are the usual marketing practices in the furniture industry, and to outline an appropriate performance framework in agreement with the procedures settled down in the ISO 9000:2000 standards.